UVB-Stimulated TNFα Release from Human Melanocyte and Melanoma Cells Is Mediated by p38 MAPK - Muthusamy, Visalini (Molecular Diversity Preservation International (MDPI), 2013)
Ultraviolet (UV) radiation activates cell signaling pathways in melanocytes. As a result of altered signaling pathways and UV-induced cellular damage, melanocytes can undergo oncogenesis and develop into melanomas. In this study, we investigated the effect of UV-radiation on p38 MAPK (mitogen-activated protein kinase), JNK and NFκB pathways to determine which plays a major role in stimulating TNFα secretion in human HEM (melanocytes) and MM96L (melanoma) cells. MM96L cells exhibited 3.5-fold higher p38 activity than HEM cells at 5 min following UVA + B radiation and 1.6-fold higher JNK activity at 15–30 min following UVB+A radiation, while NFκB was minimally activated in both cells. Irradiated HEM cells had the greatest fold of TNFα secretion (UVB: 109-fold, UVA + B: 103-fold & UVB+A: 130-fold) when co-exposed to IL1α. The p38 inhibitor, SB202190, inhibited TNFα release by 93% from UVB-irradiated HEM cells. In the UVB-irradiated MM96L cells, both SB202190 and sulfasalazine (NFκB inhibitor) inhibited TNFα release by 52%. Although, anisomycin was a p38 MAPK activator, it inhibited TNFα release in UV-irradiated cells. This suggests that UV-mediated TNFα release may occur via different p38 pathway intermediates compared to those stimulated by anisomycin. As such, further studies into the functional role p38 MAPK plays in regulating TNFα release in UV-irradiated melanocyte-derived cells are warranted.